PENEGAKAN HUKUM TERHADAP KAPAL ASING YANG MELAKUKAN PENCURIAN IKAN DI WILAYAH PERAIRAN INDONESIA BERDASARKAN UNCLOS 1982 - Samudera Kevin Perkasa; Suhaidi Suhaidi; Abdul Rahman (Journal of USU International Law, 2020)
ABSTRACT   LAW ENFORCEMENT OF FOREIGN SHIPS WHICH DO FISH THEFTING IN THE REGIONINDONESIAN WATERS BASED ON UNCLOS 1982   Illegal fishing practices are organized transnational crimes and have caused serious damage to Indonesia and other regions in the region. In addition to economic, social and ecological problems, this practice is an act that attaches the nation's territory. The main question in this study is the national law against the sinking of vessels that commit fish theft in Indonesian hunting areas. The impact of the sinking of foreign vessels conducting fish shipping in the Indonesian shipping area in the perspective of international law. Law enforcement against foreign vessels conducting voyages in the territory of Indonesian ships based on 1982 UNCLOS. This type of research or research method conducted is a normative legal research method or called legal research carried out by means of researching library materials or mere secondary data. Law Number 45 of 2009 concerning Amendment to Law Number 31 of 2004 concerning Fisheries. UNCLOS 1982 did not include the legal provisions for sinking foreign ships. The impact of the sinking of foreign vessels conducting fish shipping in Indonesian waters in the perspective of international law on the sinking of illegal foreign vessels will not affect bilateral, regional and multilateral relations between Indonesia and other countries. Law enforcement against foreign vessels that rescue fishes in Indonesian territorial waters based on 1982 UNCLOS, international law enforcement at sea is a step or prevention as well as efforts to improve and discuss compliance with international legal provisions. Keywords: Law Enforcement, Foreign Vessels, Fish Theft.[1] * Samudra Kevin P, FH Student. USU** Prof. Dr. Suhaidi, SH., M.H, USU Law Faculty Lecturer*** Abdul Rahman, S.H., M.H, USU Law Faculty Lecturer